Applied Dynamics in Engineering. - Spektor, Michael B., 1933- (Industrial Press, Inc., 2015)
This book is primarily a guide for professionals and can be used by students of Dynamics. It features 96 real-life problems in dynamics that are common in all engineering fields; including industrial, mechanical and electrical. And it uses a special table guide that allows the reader to find the solution to each specific problem. The descriptions of the solutions of problems are presented in the chapters 3 to 18. Features · The analysis of the structure of the differential equation of motion, as well as the analysis of the components that constitute this equation presented in the Chap.